Study of correlation coefficients in the productive performance of different groups in feathers color and egg quality characteristics in quail - Hadi, Haytham Mohammed Sabeeh (Journal of agricultural, environmental and veterinary sciences, 2023)
The study aimed to compare the productive performance and egg characteristics of the different groups with the color of the feathers and to estimate the correlation coefficient between the traits in quail (white, brown, and black). The results of the study showed a significant superiority in live body weight, feed consumption, number of eggs produced, and an improvement in feed conversion efficiency in favor of the 8-week-old brown group compared to the rest of the groups. White and brown outweighed the weight and mass of whites over blacks. As for the qualitative characteristics of the egg, it was noted that the brown and black colors were superior in egg width and shell thickness over the white, a highly significant negative correlation was recorded between the two characteristics of the number of eggs produced/female with the values of feed conversion efficiency -0.92 and the characteristics of egg mass and conversion efficiency diet -0.82. Describe the number of eggs produced, the mass of adult eggs 0.83, the number of eggs produced, the characteristics of egg production, weight of eggs, the mass of eggs 0.21, and the characteristics of the egg mass. And egg production was 0.27 and it had a significant positive correlation between the characteristics of the egg-laying weight and the weight of the egg-laying was 0.73 and the weight of the egg-laying with height. The albedo was 0.69 and the albedo weight and height were. It was 0.72, and there was a highly significant correlation between egg width and height 0.81.
Keywords: quail; phenotypic correlation; plumage color; productive traits